The role of postoperative hematoma on free flap compromise. (15th April 2015) - Ahmad, Faisal I.; Gerecci, Deniz; Gonzalez, Javier D.; Peck, Jessica J.; Wax, Mark K.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Hematomas may develop in the postoperative setting after free tissue transfer. When hematomas occur, they can exert pressure on surrounding tissues. Their effect on the vascular pedicle of a free flap is unknown. We describe our incidence of hematoma in free flaps and outcomes when the flap is compromised. Study Design Retrospective chart review of 1, 883 free flaps performed between July 1998 and June 2014 at a tertiary referral center. Methods Patients with free flap compromise due to hematoma were identified. Etiology, demographic data, and outcomes were evaluated. Results Eighty‐eight (4.7%) patients developed hematomas. Twenty (22.7%) of those had flap compromise. Twelve compromises (60%) showed evidence of pedicle thrombosis. The salvage rate was 75% versus 54% in 79 flaps with compromise from other causes (P = .12). Mean time to detection of the hematoma was 35.3 hours in salvaged flaps compared to 91.6 hours in unsalvageable flaps (P = .057). Time to operating room (OR) from detection was 2.8 hours in salvageable flaps compared to 12.4 hours in nonsalvageable flaps (P = .053). The salvage rate for flaps that returned to the OR in <5 hours was 93.3% compared to 20% (P = .0049) for those that did not. Vascular thrombosis reduced salvage rate to 58.3% from 100% (P = .002) when there was no thrombosis. Conclusions In our series hematomas developed rarely. When they did, 23% went on to develop flap compromise. Prompt recognition and re‐exploration allowed for a high salvage rate. Vessel thrombosis predicted inability to salvage the flap. Level of Evidence 4 Laryngoscope, 125:1811–1815, 2015